Hacking Threat in Arab Cyberspace: Appraisal Analysis on Al-Hakirz Al-Muslimun’s Hacktivism Narratives - Reflinaldi, Reflinaldi; Rahmi, Awliya; Rezi, Melisa; Syahidin, Amal (Universitas Pendidikan Mandalika, 2024)
This research aims to describe the negotiation of the attitude of the hacker group الهاكرز المسلمون (al-hākirz al-muslimūn) 'Muslim hackers' (MH) in the narrative of their hacking threats to the governments of Sweden, Australia and Israel. A descriptive-explanatory design was applied by taking three hacking threat videos on the YouTube channel